Traditional medicinal plants used by the Temuan Villagers in Kampung Tering, Negeri Sembilan, Malaysia - Ong, H.C.; Ahmad, N.; Milow, P. (2011)
The authors report a total of 35 species of medicinal plants used by the villagers in Tering village. 20 species (57%) were native plants while 15 species (43%) were cultivated plants. The plants were used to treat various kinds of ailments and other health problems normally Faced by these people. The common mode of administration was oral (54.3%) followed by external use (37.1%). Decoction was the more common method of preparing herbal medicine (48.6%) followed by pounded or mashed (25.7%). The plants were used to treat many types of ailments ranging from simple ones such as joint aches and pains to serious ailments such as bone fractures. hypertension and tumors. Traditional knowledge and usage of medicinal plants is decreasing due to various Factors such as modern medicines are easily available. the younger generation are less interested in folk medicine, changes in habitat causing certain medicinal plants to be unavailable or less available.